Asia and postwar Japan deimperialization, civic activism, and national identity - Avenell, Simon Andrew (Harvard University Asia Center, 2022)
"Traces the unfolding of Japan's postwar Asia problem through various phases of deimperialization from 1945 until the early twenty-first century. It focuses on the thought and activism of progressive activists and intellectuals as they struggled to overcome rigid preconceptions about 'Asia,' as they grappled with the implications of postimperial responsibility, and as they forged new regional solidarities and Asian imaginaries"
Includes bibliographical references and index
Keywords: Geschichte 1945-2000; Intellektueller; Aktivist; Ostasien; Japan; Imperialism; Decolonization / Asia; Political activists / Japan / History / 20th century; Nationalism / Japan / History / 20th century; Japan / Relations / Asia; Asia / Relations / Japan; Japan / Foreign relations / 1945-